BUDAYA POLITIK WARUNG KOPI WILAYAH PESISIR DI BUMI TEUKU UMAR MENJELANG PEMILU 2019 - Egi Saputra; Eko Sanovyanto; Lisantri Lisantri; Alimas Jonsa (Jurnal Public Policy, 2019)
This study titled about the political culture of the coffee shop in the coastal areas Teuku Umar before the election in 2019,As for the formulation in the research is how is the political culture of coastal area coffee shops in Teuku Umar Areas Meulaboh West Aceh, and What are the indicators that support politics in the coastal coffee shops that become a political culture in coffee shops.The methodology used in this research is qualitative research methodology, with a descriptive and phenomenological approach, so that in this study the researchers found that coffee shops in the city of Meulaboh had become a political forum utilized by political actors to gain votes in the 2019 general election. This is supported by the coffee shop as a gathering place for the whole community and as a place to discuss and exchange information. Keyword: Culture, Political, and Coffee Shop